Combined Methods (Formal Adjusted Indirect Comparison, Meta-Analysis and Principal Component Analysis) Comparisons of the Safety and Efficacy of Ambrisentan, Bosentan, and Sildenafil in the Patients With Pulmonary Arterial Hypertension - Li, Xinmei; Li, Te (Frontiers in Pharmacology, 2020)
Background Three oral drugs (ambrisentan, bosentan, and sildenafil) have been widely used to treat patients with pulmonary arterial hypertension (PAH). 1) There are no studies that directly compare the safety and efficacy of these three drugs. Existing studies could not meet the physician’s need to select the most beneficial drugs for patients. 2) Principal component analysis is mainly used for scale analysis and has not been reported in clinical field. 3) When the results of the indirect meta-analysis were not satisfactory, no new solutions have been proposed in existing meta-analysis studies. Methods The overall process of this study is divided into 4 steps 1) literature search and data extraction; 2) principal component analysis; 3) common reference-based indirect comparison meta-analysis; 4) formal adjusted indirect comparison. Results Nine randomized controlled trials (RCTs) experiments and eight long-term experiments were selected. The main influencing factors are mortality, 6-min walk distance (6MW), mean pulmonary arterial pressure (PAP), cardiac index (CI) by principal component analysis. There was no significant heterogeneity among the indirect meta-analysis of three drugs. But in the formal adjusted indirect comparison 1) the level of PAP of sildenafil group (60.5 ± 22.35, 220) was higher than that of the other three groups, placebo (53.5 ± 17.63, 507) (p < 0.001), ambrisentan (49.5 ± 15.08, 130) (p < 0.001), and bosentan (54.6 ± 118.41, 311) (p < 0.001); 2) the level of CI of sildenafil group (54 ± 18, 311) was higher than that of the other three groups, placebo (2.7 ± 1.09, 518) (p < 0.001), ambrisentan (2.5 ± 0.75, 130) (p < 0.001), and bosentan (2.5 ± 1.06, 333) (p < 0.001). In addition, sildenafil significantly improved the survival rate comparing with ambrisentan and bosentan. Conclusions The results of this study suggest that sildenafil might be more suitable for long-term treatment of PAH patients than ambrisentan and bosentan. In order to enable clinicians to draw conclusions more quickly and directly in the data-rich literature, we suggest the use of principal component analysis combined with formal adjusted indirect comparison to compare the efficacy and safety of drugs.